Sretno dijete . Lucky Kid - Mirković, Igor (Gerila DV Film ; Grlić, Rajko, 2003)
In this documentary, Igor Mirković, originally a news reporter, portrays the emergence of the independent, vibrant new wave punk-rock musical scene in Zagreb, ex-Yugoslavia, emerging at the end of the 1970s and the beginning of the 1980s. Most of the documentary consists of his interviews with Zagreb rock singers and other important actors on the scene as well as with some of their Belgrade counterparts. With plenty of original musical and archival images from the period, the film makes no claim to objectivity, but is rather a monument to the generation that grew up in the belief that rock’n’roll is larger than life. The story is narrated from the perspective of an outsider since the author was just a teenager when the scene exploded and is concerned with illustrating the life-long influence of rock-music on his way of life. Through Zagreb, Ljubljana, Vienna, Belgrade, Budapest, Paris, Utrecht and New York, the author thus finds himself in pursuit of the heroes of his youth. Mirković also implicitly tried to interconnect his rock story with the fall of socialism: he provides a historical background by bringing in important political moments of the period such as the death of Tito or the evolving economic crisis.